Methodological design for the development of strategies to improve the quality of life of artisans: A study in Southeast Mexico - Barroso Tanoira, Francisco Gerardo (2024)
The objective of this paper was to propose, based on a literature review, strategies for improving quality of life of artisans in section 2 of the Mayan Train (municipalities of Calkiní, Hecelchakán and Tenabo, in the state of Campeche). Although this study is focused in these three municipalities, it would settle a methodological precedent in the region and would generate new evidence for supporting including policies to improve quality of life in these vulnerable populations.